Effectiveness Through Crime Investigation Complaint Case Holds In Central Java Police Jurisdiction - Yuniar Pradhana Mukti; Gunarto Gunarto (Jurnal Daulat Hukum, 2018)
Problems of criminal law, especially the problem of crime, abuse and all kinds of acts that fall into the category of offense is now becoming one of the crucial problems and quite tricky to overcome. In line with the task of institution Indonesian National Police (INP) in an effort to maintain security and order and enforcement of justice citizens, then the effectiveness of the investigation and the disclosure of a criminal offense it is important to be maximized. The aim is to give meaning to the rule of law in Indonesia that provides fairness, expediency and legal certainty.Keywords: Criminal Law; Police; Effectiveness; Law Enforcement